Analisis Kesalahan Newman dalam Menyelesaikan Soal Cerita Materi Statistika Ditinjau dari Adversity Quotient - Kurnia, Puspita Dwi; Subarinah, Sri; Kertiyani, Ni Made Intan; Sarjana, Ketut (FKIP Universitas Mataram, 2024)
This research aims to describe the errors made by students based on their Adversity Quotient (AQ) while solving story problems in statistics. This study is qualitative in nature with a descriptive approach. The subjects of this research are 25 students from class VIII A at SMP Negeri 1 Kediri. The instruments used include an AQ questionnaire, a written test on statistics, and an interview guideline. Based on the research findings, students categorized as AQ quitters and campers mostly made similar errors, including transformation errors, process skill errors, and encoding errors, however, quitters exhibited a higher error rate. Meanwhile, students with AQ climber types primarily made encoding errors. Transformation errors occurred because students did not understand the problems, were unsure how to convert the information from the questions into mathematical forms, and lacked knowledge of the formulas needed to solve the problems. Process skill errors were attributed to students' lack of understanding of the problems, insufficient grasp of the material concepts, and unawareness of the steps required to solve the questions. Encoding errors were caused by mistakes made in previous stages, students' lack of attention to detail, and rushing to write the final answers on the answer sheets.